2021
DOI: 10.1111/area.12726
|View full text |Cite
|
Sign up to set email alerts
|

Capturing a moving target: Interviewing fintech experts via LinkedIn

Abstract: This paper explores possible responses to some of the main challenges associated with conducting elite and expert interviews as part of qualitative research in human geography. Drawing on the example of the dynamic fintech industry, the paper outlines some similarities and differences between elite and expert interviews and uses this to identify and discuss possible responses. Against this backdrop, the paper also reflects on advantages and disadvantages of using the professional social networking site LinkedI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…However, we found that this was eased by the unique context of the pandemic, because all involved were unfamiliar with remote working and were learning to use new technologies together. This made the position of ‘expert’ more fluid than it would be ordinarily and softened the positioning of expert participants as holders of knowledge ‘not otherwise available’ (Robinson, 2021: 673) or researchers as being ‘emotionally detached’ and ‘in control’ (Nilan, 2002: 372). For us, conducting focus groups, interviews and ethnographic activities via video platforms, when all involved were in their own homes, disrupted the power inherent in the researcher/researched relationship in ways that we can learn from for future social research.…”
Section: The Research Contextmentioning
confidence: 99%
“…However, we found that this was eased by the unique context of the pandemic, because all involved were unfamiliar with remote working and were learning to use new technologies together. This made the position of ‘expert’ more fluid than it would be ordinarily and softened the positioning of expert participants as holders of knowledge ‘not otherwise available’ (Robinson, 2021: 673) or researchers as being ‘emotionally detached’ and ‘in control’ (Nilan, 2002: 372). For us, conducting focus groups, interviews and ethnographic activities via video platforms, when all involved were in their own homes, disrupted the power inherent in the researcher/researched relationship in ways that we can learn from for future social research.…”
Section: The Research Contextmentioning
confidence: 99%
“…Such suspicions are discussed frequently within methodological literatures on elite interviewing, which often emphasise the difficulties involved in convincing interviewees accustomed to speaking publicly on behalf of their organisations to do more than reiterate the 'official' accounts of their (and their organisations') activities and agendas contained in publicly-available documents such as marketing brochures and policy statements (Rice, 2010). Geographers preparing to interview government officials, financiers or corporate managers like Nick are regularly warned that these people will likely be experienced or even professionally trained in directing conversations in order to present themselves and their employers in a positive light (Desmond, 2004).…”
Section: Artful Elitesmentioning
confidence: 99%
“…I stressed how important it was for the project that I understood the role played by large retailers (like their firm) in preventing or preparing for disruptions to food provisioning systems and emphasised that their first‐hand experience of these activities made them uniquely able to impart this understanding. I thus positioned Nick and his colleagues implicitly as ‘expert’ interviewees—individuals who were significant to my research because they possessed specialist knowledge about important processes and practices within an influential organisation (Robinson, 2021). However, approaching my interviewees as experts also implicitly established certain expectations about the purpose of our discussions.…”
Section: Informed Expertsmentioning
confidence: 99%
See 1 more Smart Citation
“…In doing so, we illustrate how informational and financial geographies, while closely linked and sometimes matching, are distinct elements of global networks of money, and suggest that disentangling them is crucial. Therefore, this article employs a qualitative analysis of multidisciplinary secondary data, including literature from economic and financial geography, business studies, political economy, critical data studies and science and technology studies, as well as industry reports and insights from 30 expert interviews across the banking and payments industry (Robinson, 2021).…”
Section: Introductionmentioning
confidence: 99%